2012
DOI: 10.1007/s00482-011-1125-1
|View full text |Cite
|
Sign up to set email alerts
|

Besteht ein Zusammenhang zwischen Rückenschmerz und der Stabilität der lumbalen Wirbelsäule in der Schwangerschaft?

Abstract: During pregnancy approximately 50% of women suffer from low back pain (LBP), which significantly affects their everyday life. The pain could result in chronic insomnia, limit the pregnant women in their ability to work and produce a reduction of their physical activity. The etiology of the pain is still critically discussed and not entirely understood. In the literature different explanations for LBP are given and one of the most common reasons is the anatomical changes of the female body during pregnancy; for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…Increased motion in the pelvic joints diminishes the efficiency of load transmission and increases shear forces across the joints, resulting in pelvic girdle pain in pregnant women 63 . Additionally, there is an increase in the sagittal moment due to the enlarged fetus and uterus, resulting in hyperlordosis 64 . One study found that pregnant women with pelvic girdle pain had lower back flexor endurance values than those without pain 65 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased motion in the pelvic joints diminishes the efficiency of load transmission and increases shear forces across the joints, resulting in pelvic girdle pain in pregnant women 63 . Additionally, there is an increase in the sagittal moment due to the enlarged fetus and uterus, resulting in hyperlordosis 64 . One study found that pregnant women with pelvic girdle pain had lower back flexor endurance values than those without pain 65 .…”
Section: Discussionmentioning
confidence: 99%
“… 63 Additionally, there is an increase in the sagittal moment due to the enlarged fetus and uterus, resulting in hyperlordosis. 64 One study found that pregnant women with pelvic girdle pain had lower back flexor endurance values than those without pain. 65 A case–control study showed that pregnant women adapted to their patterns of lumbar motion and erector spinae activity during flexion and extension.…”
Section: Discussionmentioning
confidence: 99%
“…14 To compensate for the increased load, most mothers will adopt an exaggerated lumbar lordosis while standing. 15 As the lumbar spine moves into greater extension, the sacrum moves into greater nutation, 16 and as a result, the compression loads acting on the SIJ when in upright postures are increased.…”
Section: Discussionmentioning
confidence: 99%
“…Bipedalism and lumbar lordosis are often regarded as a cause of low back pain, through the increased spinal shearing forces and increased risk of spondylolisthesis [4,8,16,29,30]. In this respect it is of utmost importance to understand the function of lumbar lordosis.…”
Section: Discussionmentioning
confidence: 99%